English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I know that if x=-t then multiply both sides by -1.
In this problem I am thinking you multiply both side by (ln) the natural log to eliminate the e and the answer is t= ln(x).

2007-03-02 04:47:02 · 4 answers · asked by houstonman20042002 1 in Science & Mathematics Mathematics

4 answers

Ln is a function (an Unary operator.)
it cannot be multiplied.
Ln is natural LOG i.e. log with base 'e'


for x=e^t,
is multiplied with a number(scalar) ,say 2 it will become
2x=2e^t

but by taking ln on both sides we get:
L.H.S=ln(x)
r.h.s=ln(e^t)

=t*ln(e) in this step the power of 'e' comes down as an index.

=t as ln(e)=1.

for better details refer to LOGARITHM chapters in text

2007-03-02 04:57:54 · answer #1 · answered by Mac 1 · 0 0

If my memory is correct ....

log x = t * log e
therefore

t = log x/log e

2007-03-02 04:51:35 · answer #2 · answered by Kenny 3 · 1 1

x=e^t
LN(x)=LN(e^t )=tLN(e)=t(1)=t

2007-03-02 04:54:20 · answer #3 · answered by fcas80 7 · 1 0

What you think is what's correct.

2007-03-02 04:54:24 · answer #4 · answered by Tim 4 · 1 0

fedest.com, questions and answers